A biomechanical comparison in the lower limb and lumbar spine between a hit and drag flick in field hockey - Ng, L.; Rosalie, S.; Sherry, D.; Loh, W. B.; Sjurseth, A. M.; Iyengar, S.; Wild, C. Y. (Journal of Sports Sciences, 2019)
Research has revealed that field hockey drag flickers have greater odds of hip and lumbar injuries compared to non-drag flickers (DF). This study aimed to compare the biomechanics of a field hockey hit and a specialised field hockey drag flick. Eighteen male and seven female specialised hockey DF performed a hit and a drag flick in a motion analysis laboratory with an 18-camera three-dimensional motion analysis system and a calibrated multichannel force platform to examine differences in lower limb and lumbar kinematics and kinetics. Results revealed that drag flicks were performed with more of a forward lunge on the left lower limb resulting in significantly greater left ankle dorsiflexion, knee, hip and lumbar flexion (Ps<0.001) compared to a hit. Drag flicks were also performed with significantly greater lateral flexion (P < 0.002) and rotation of the lumbar spine (P < 0.006) compared to a hit. Differences in kinematics lead to greater shear, compression and tensile forces in multiple left lower limb and lumbar joints in the drag flick compared to the hit (P < 0.05). The biomechanical differences in drag flicks compared to a hit may have ramifications with respect to injury in field hockey drag flickers.